ANALISIS PENGARUH PEMASANGAN GROUND ROOT PARALEL PADA NILAI TAHANAN PENTANAHAN JARINGAN DISTRIBUSI 20 KV PT. PLN (PERSERO) ULP BUMIAYU - Isnu Gita Kumara; Rizki Noor Prasetyono; Randi Adzind Murdiantoro (Journal of Electronic and Electrical Power Applications, 2022)
The grounding system is an direct protection against instrumentality that uses electricity as a source of power from overcurrent and leakage current or usually caused by lightning. Measurement of the value of grounding resistance is carried out every 6 months to maintan the resistance value of the grounding system to meet PUIL standards. For the grounding system theat has a resistance value above 5 Ohm, it is necessary to add a ground root that is connected in parallel. The resistance value data before and after the addition of the gorund root will then be carried out a simple linear regression analysis using software SPSS 25.0 for windows. The analysis method used in this study is quantitative analysis method to find out whether or not the effect of additional ground root on the grounding resistance. Based on the output model coefficient on SPSS, it showed a significance value of less than 0.05 which means the addition of a parallel ground root had an effect on the value of grounding risistance or could improve the grounding resistance. The output of summary model showed a correlation value (R) of 0.639, which means that the independent variable and the dependent variable had a strong relationship, while the value of R Square or the percentage of the effect of adding ground root to the value of grounding resistance was 40,9% while the other59,1% was influenced by other unexamined factor.